2016
DOI: 10.1080/21678707.2016.1240613
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological therapeutics targeting the secondary defects and downstream pathology of Duchenne muscular dystrophy

Abstract: Introduction Since the identification of the dystrophin gene in 1986, a cure for Duchenne muscular dystrophy (DMD) has yet to be discovered. Presently, there are a number of genetic-based therapies in development aimed at restoration and/or repair of the primary defect. However, growing understanding of the pathophysiological consequences of dystrophin absence has revealed several promising downstream targets for the development of therapeutics. Areas covered In this review, we discuss various strategies for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 190 publications
(202 reference statements)
2
36
0
Order By: Relevance
“…However, less results were obtained in terms of recovery of muscle function and quality of life improvement [47]. The side effects emerged in the clinical trials testing new agents in both dystrophic [46,68] and cancer patients [47] represent another important issue in the treatment of MDs and CAC. Taken together, these evidences highlight the need for additional studies aimed to further investigate the molecular mechanisms orchestrating muscle wasting in chronic diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, less results were obtained in terms of recovery of muscle function and quality of life improvement [47]. The side effects emerged in the clinical trials testing new agents in both dystrophic [46,68] and cancer patients [47] represent another important issue in the treatment of MDs and CAC. Taken together, these evidences highlight the need for additional studies aimed to further investigate the molecular mechanisms orchestrating muscle wasting in chronic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Besides pharmacological and gene therapy approaches adopted in the treatment of MDs [1,3,18,46], in the last years, preclinical studies in murine and canine models investigated the myogenic potential of muscle precursors, such as satellite cells (SC), skeletal myogenic precursors (SMPS), muscle side population (SP), fibro-adipogenic progenitors (FAPs), and mesoangiblasts (MABs) [1,3,21]. These studies revealed new potential therapeutic perspectives for the treatment of MDs based on muscle progenitor cell transplantation as revealed by numerous interventional trials [21].…”
Section: Mdsmentioning
confidence: 99%
“…Full-length dystrophin is a large rod-shaped protein in association with the formation of DGC which connects the subsarcolemmal F-actin cytoskeleton to the basal lamina of the extracellular matrix, stabilizing membrane during repeated cycles of contraction and relaxation 12,13 . Besides, The DGC also has an essential role in cell signaling apart from mechanical function.…”
Section: Pathogenesis Studiesmentioning
confidence: 99%
“…Dystrophin is a key component of the dystrophin-associated protein complex (DAPC), which serves as a stabilizing link between the cytoskeleton and extracellular matrix during muscle fiber contraction. Loss of dystrophin and DAPC function makes muscle cell membranes susceptible to contraction-induced damage and leads to progressive calcium dysregulation, satellite cell dysfunction, inflammation, fibrosis, and necrosis (reviewed in Allen et al, 2016 and in Spinazzola and Kunkel, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…DMD gene therapy and gene editing approaches are very promising but face many challenges (Chamberlain and Chamberlain, 2017; Conboy et al, 2018; Duan, 2018; Min et al, 2019). Many small molecule approaches are being identified that could benefit DMD by modulating different pathological mechanisms downstream of the dystrophin mutation (Crone and Mah, 2018; Guiraud and Davies, 2017; Hoffman, 2019; Spinazzola and Kunkel, 2016). A current view in the DMD field is that a combination of therapies targeting different pathological mechanisms may ultimately be most beneficial for patients (Guiraud and Davies, 2017; Hoffman, 2019).…”
Section: Introductionmentioning
confidence: 99%